Pathologists' Participation and Performance in the Medicare Physician Quality Reporting System. (11th September 2019) - Ge, Li; Liu, Xinliang
Abstract: Objectives: Public reporting of quality metrics has become increasingly important for pathologists to demonstrate excellence of care and to secure value-based payments from both public and private payers. This study evaluated the participation and performance of pathologists in the Medicare Physician Quality Reporting System (PQRS). Methods: This study conducted a retrospective review of the Physician Compare data files from 2016. Specifically, pathologists enrolled in the Physician Compare Initiative were identified and merged with quality data using uniquely assigned National Provider Identifiers. Descriptive statistics and multiple logistic regression were performed using Stata (version 12.1) statistical software (StataCorp, College Station, TX). Results: Among the 11, 637 pathologists identified in the Physician Compare Initiative, 8, 408 pathologists (73.3%) participated in the PQRS. Regression analysis indicated that female gender, foreign medical graduate (FMG), and a larger number of employees in the affiliated organization were associated with a lower likelihood of participating in the PQRS. To protect patient privacy, the Centers for Medicare and Medicaid Services (CMS) only released the quality metrics of 353 pathologists, which were computed based on 20 or more Medicare beneficiaries. The three most commonly reported quality metrics included PQRS#249 Barrett's Esophagus, PQRS#395 Lung Cancer Reporting (Biopsy/Cytology Specimens), and PQRS#397 Melanoma Reporting. The mean performance rates for the three most common metrics were 98.8% (SD 8.3%), 96.8% (SD 11.9%), and 97.4% (SD 6.9%), respectively. Conclusion: A majority of pathologists participated in the Medicare PQRS program in 2016. The performance rates of public available quality metrics remained at high levels with significant variations in some metrics. Future research should examine the quality performance of pathologists as they transition from the PQRS to the Merit-based Incentive Payment System (MIPS) under the Quality Payment Program.